REDOX ZONATION: EQUILIBRIUM CONSTRAINTS ON THE FE(III)/SO4-REDUCTION INTERFACE - Postma D.; Jakobsen R. (My University, 1996)
The concept of redox zonation during degradation of organic matter, which is usually explained by the overall energy yield of different reactions, has been reevaluated. At least for reduction of Mn(IV), Fe(III), sulfate, and methanogenesis, the sequential occurrence of these processes is much easier explained by a partial equilibrium approach where the fermentive step is overall rate limiting, while the electron accepting processes are considered to be close to equilibrium.Using the partial equilibrium approach, an explanation is sought for the simultaneous occurrence of Fe(III) and sulfate reduction, observed in several field studies. Calculations of conditions for equilibrium between Fe(III) and sulfate reduction indicate that, depending on the stability of the iron oxide, simultaneous reduction of Fe(III) and sulfate is thermodynamically possible under a wide range of sedimentary conditions and sulfate reduction may even occur before Fe(III) reduction. In Fe2+-rich environments, the pH of the porewater has in addition a strong influence on whether Fe(III) or sulfate reduction is favored. In natural sediments, the presence of a wide range of iron oxide stabilities is likely to cause considerable overlap between zones of Fe(III) and sulfate reduction, while a better confined stability range of iron oxides should cause more distinct zones of Fe(III) and sulfate reduction.